Description of Two New Species of the Genus Vorticella (Ciliophora: Peritrichia) Epibionts on Pomacea canaliculata (Mollusca: Ampullariidae: Gastropoda) in Southern Brazil - Pereira, Marcos W. O.; de Brito, Fabiano Carvalho; Eizirik, Eduardo; Utz, Laura R. P. (Zootaxa, 2018)
The peritrich ciliates Vorticella veloxiiforme n.sp. and Vorticella ampullaria n.sp. were found as epibionts on the ampullarid mollusk Pomacea canaliculata collected from Patos Lagoon, Rio Grande do Sul state, Brazil. The detailed morphology of both species was investigated using live and stained specimens, as well as scanning electron microscopy. Zooids of Vorticella veloxiiforme are cup shaped measuring 57 X 41 μm on average. A J-shaped macronucleus lies in the upper half of the cell. One contractile vacuole was observed in the upper part of the cell. V. ampullaria presents an elongate zooid measuring 70 X 25 µm on average. A C-shaped macronucleus lies in the middle of the cell. Two contractile vacuoles are present: one close to the peristome and the other in the lower half of the cell. The pattern of oral polykinetids was typical of the genus, with all infundibular polykinetids composed by three rows of kinetosomes each. SEM revealed a regular pattern of pores present on the zooid membrane of both species. Analyses of the 18s rDNA placed the two new species in the order Vorticellida close to described species of Vorticella.